Thermal treatment method: a novel approach to prepare Nd0.7Sr0⋅3MnO3 manganite - Hon, X. T.; Lau, L. N.; Lim, K. P.; Wong, Y. J.; Ishak, A. N.; Awang Kechik, M. M.; Chen, S. K.; Shabdin, M. K.; Shaari, A. H. (Elsevier, 2023)
The discovery of colossal magnetoresistance (CMR) in perovskite manganites has attracted considerable interest due to their utilisation in spintronic devices. Various techniques were adopted to investigate the influence of their particle size on magnetic and transport properties. Unfortunately, the complexity of conventional methods underlines the need for a simple preparation technique. Here, single phase Nd0.7Sr0⋅3MnO3 (NSMO) was successfully synthesised by thermal treatment method with polyvinylpyrrolidone (PVP) acting as capping agent. FTIR spectra confirmed the decomposition of PVP after a high-temperature sintering process. The atomic composition of the sample was found very close to the nominal ratio. NSMO exhibited paramagnetism at room temperature, and its TC was recorded at 246 K. Typical CMR behaviour was perceived and accompanied by metal-insulator transition (TMI) at 182 K. Thus, this study has provided a novel approach to prepare high-purity Nd-based manganite with an easier operation.